New Trends and Future Perspectives in the Diagnosis of Urothelial Carcinoma: A Comprehensive Review of the Literature - Mourmouris Panagiotis; Georgopoulos Ioannis; Klapsis Vasilleios; Pisiotis Nikolaos; Salmas Ioannis; Charamoglis Sotirios (Medicina)
Despite the high incidence of bladder cancer (it represents the 7th most common cancer in males), EAU guidelines do not recommend any technique for screening and prevention, whereas the main diagnostic tools remain computed tomography urography (CTU), cytology, and cystoscopy. Unfortunately, these gold-standard modalities are mainly characterized by low sensitivity and accuracy. To minimize the limitations and increase the detection rates of urothelial cancer, several technologies have been developed. In our review, we summarize all the available data concerning the contemporary technological novelties that include imaging, cytology, and endoscopic techniques in pursuit of finding the optimal combination of diagnostic tools that can provide better detection accuracy.